Necesitatea unei reglementări legislative a instituţiei străpungerii vălului corporative//The regulatory role in regard to the subject of piercing of the corporate veil - Roxana Alexandra Istudor (Analele Ştiinţifice ale Universităţii "Al.I. Cuza" din Iaşi. Ştiinţe Juridice, 2022)
The approach to the concept of piercing the corporate veil was criticized in Romania for its lack of principles and because it does not ensure enough guarantees against the abuse of legal personality. This article aims to compare the practice of three different jurisdictions that regulated the principles which safeguard the limited liability of companies and to show the advantages and disadvantages of having one common legal framework in order to propose a better solution for regulating corporate law in our country.